Biochemical Evidence for Formate Transfer in Syntrophic Propionate-Oxidizing Cocultures of Syntrophobacter fumaroxidans and Methanospirillum hungatei - de Bok, Frank A. M. (American Society for Microbiology, 2002)
The hydrogenase and formate dehydrogenase levels in Syntrophobacter fumaroxidans and Methanospirillum hungatei were studied in syntrophic propionate-oxidizing cultures and compared to the levels in axenic cultures of both organisms. Cells grown syntrophically were separated from each other by Percoll gradient centrifugation. In S. fumaroxidans both formate dehydrogenase and hydrogenase levels were highest in cells which were grown syntrophically, while the formate-H(2) lyase activities were comparable under the conditions tested. In M. hungatei the formate dehydrogenase and formate-H(2) lyase levels were highest in cells grown syntrophically, while the hydrogenase levels in syntrophically grown cells were comparable to those in cells grown on formate. Reconstituted syntrophic cultures from axenic cultures immediately resumed syntrophic growth, and the calculated growth rates of these cultures were highest for cells which were inoculated from the axenic S. fumaroxidans cultures that exhibited the highest formate dehydrogenase activities. The results suggest that formate is the preferred electron carrier in syntrophic propionate-oxidizing cocultures of S. fumaroxidans and M. hungatei.